Pathogenicity of filamentous fungi towards Atta sexdens rubropilosa (Hymenoptera:﻿ ﻿Formicidae﻿) - Cardoso, Sandra Regina Sousa [UNESP] (2022)
In the Neotropics, leaf-cutting ants are pests of great importance to various crops. The natural defenses and complexity of these ants reduce the impact of potentially useful pathogens for biological control. Furthermore, several types of research with entomopathogenic fungi usually focus on only a few isolates of well-known species, like Beauveria bassiana and Metarhizium anisopliae, in addition to not always use isolates obtained from leaf-cutting ants. Here, we evaluated the pathogenicity of several filamentous fungi to workers of the leaf-cutting ant Atta sexdens rubropilosa. For that, we used fungi previously isolated in an extensive isolation study in Atta spp. reproductive females. Conidia suspensions of Aspergillus flavus, B. bassiana, Isaria fumosorosea and Purpureocillium lilacinum were prepared to a final concentration of 108 conidia mL− 1. In addition, we included sterilized distilled water as control and commercial B. bassiana as standard. Ant workers were immersed in these treatments for eight seconds. The number of dead workers was counted daily. Several fungal isolates killed more, or faster than the standard B. bassiana, showing that they may have a better potential for use in leaf-cutting ants´ biological control. Additionally, the present study reports for the first time the pathogenicity of P. lilacinum and I. fumosorosea towards Atta workers. Thus, we showed that an extensive and specific prospection is of importance for the development of biopesticides for leaf-cutting ants control.